NIGERIA TECHNICAL AID CORPS (TAC) AND NATIONAL INTEREST, 1999-2023: AN ASSESSMENT - AGABA HALIDU; EMMANUEL IDEMOR UKHAMI; SOLOMON BABATUNDE KUMAPAYI; AKINOLA JACOB ASHIMOLOWO (International Studies Journal)
This paper assesses the impact of Nigeria's Technical Aid Corps (TAC) on the country's national interest from 1999 to 2023. TAC is a pivotal element of Nigeria's foreign policy, established to provide technical assistance to developing nations in Africa, the Caribbean, and the Pacific. This paper examines the program’s effectiveness in advancing Nigeria's diplomatic, economic, and socio-political objectives. The study adopted qualitative data from books, journals, official data, and the Internet, and the soft power theory was considered in advancing the essence of establishing TAC. Findings indicate that TAC significantly enhances Nigeria's diplomatic relations and international image, promotes trade and investment, and contributes to capacity building and regional stability. However, the program faces challenges such as logistical constraints, political instability, and economic limitations. The research provides practical recommendations for improving TAC's operational framework and strategic alignment with Nigeria's foreign policy goals. This assessment not only contributes to the academic discourse on international aid and national interest but also offers actionable insights for policymakers to optimize the impact of TAC in fostering sustainable development and enhancing Nigeria’s global influence.